Elective Tracheal Intubation With the VieScope—A Prospective Randomized Non-inferiority Pilot Study (VieScOP-Trial) - Petzoldt, Martin; Engels, Yasmin; Popal, Zohal; Tariparast, Pischtaz A.; Sasu, Phillip B.; Brockmann, Andrés; Punke, Mark A.; Grensemann, Jörn (Frontiers in Medicine, 2022)
Background Tracheal intubation is commonly performed after direct laryngoscopy using Macintosh laryngoscopes (MacL), but visualization of the larynx may be inadequate. The VieScope (VSC) as a new type of laryngoscope consisting of a straight, shielded, illuminated tube used to perform intubation via a bougie was investigated in this prospective randomized trial in patients without expected difficult airways. Methods With ethics approval, 2 × 29 patients for elective surgery were randomized 1:1 to intubation with VSC or MacL. Endpoints were first attempt success rates (FAS), Percentage of Glottis Opening Scale (POGO), time to intubation (TTI), and difficulty ratings on visual analog scales (0–100, lower values better). Data are given as mean ± standard deviation. Results The FAS was 83 ± 38% for VSC and 86 ± 34% for MacL (P = 0.723). For VSC, POGO was 86 ± 17% and for MacL 68 ± 30% (P = 0.007). TTI for VSC was 93 ± 67s vs. 38 ± 17 for MacL (P < 0.001). Difficulty of intubation was rated 23 ± 22 for VSC vs. 18 ± 22 for MacL (P = 0.422), viewing conditions 12 ± 15 vs. 24 ± 25 (P = 0.031), and difficulty of tube placement was rated 27 ± 30 vs. 7 ± 8 (P = 0.001). Conclusion No difference in FAS was detected between VSC and MacL. Visualization of the larynx was superior using the VSC, while TTI was prolonged and tube placement via bougie was more challenging. The VSC could be an alternative to MacL in patients with difficult laryngoscopy, but this should be investigated further in patients with expected difficult airways.